Current Advances and Future Directions in Behavior Assessment. (March 2017) - Riley-Tillman, T. Chris; Johnson, Austin H.
Multi-tiered problem-solving models that focus on promoting positive outcomes for student behavior continue to be emphasized within educational research. Although substantial work has been conducted to support systems-level implementation and intervention for behavior, concomitant advances in behavior assessment have been limited. This is despite the central role that data derived from behavior assessment methods must play in making defensible multi-tiered decisions such as those for screening and progress monitoring. In this commentary, the role of assessment in the evidence-based practice movement is described, alongside necessary features of behavior assessment methods utilized in multi-tiered systems. The relevance of these features to articles in this special issue is described. Finally, observations and suggestions for future directions regarding the current state of behavior assessment in educational research are offered.